2003
DOI: 10.1177/082585970301900404
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Bad News: Impact of a Continuing Medical Education Workshop

Abstract: I Objective:To evaluate the impact of an interactive continuing medical education workshop designed to help physicians in breaking bad news to their patients. Methodology: Analysis of post-workshop questionnaires from 539 physicians assessing the retention of the key concepts and the perception of the potential impact of the workshop on their practice immediately after the workshop and six months later. Results: The most significant concepts retained by the respondents are: the need to take into consideration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…As regards participant-based outcomes, positive effects were reported in terms of participant satisfaction with course [43,46,47], reported improvements in communication skills [46,56], increased knowledge [46,48], confidence [42,47,51], attitudes and beliefs [41,53 •• ], and comfort in difficult situations [42]. Increased satisfaction of participants with the interview after completing the course was also found in some studies [53 •• ,55 • ] but not in others [49,50,58 •• ].…”
Section: Assessment Toolsmentioning
confidence: 98%
“…As regards participant-based outcomes, positive effects were reported in terms of participant satisfaction with course [43,46,47], reported improvements in communication skills [46,56], increased knowledge [46,48], confidence [42,47,51], attitudes and beliefs [41,53 •• ], and comfort in difficult situations [42]. Increased satisfaction of participants with the interview after completing the course was also found in some studies [53 •• ,55 • ] but not in others [49,50,58 •• ].…”
Section: Assessment Toolsmentioning
confidence: 98%
“…13 In a study based on the questionnaire during the post-OSCE2 occurring 6 months after the course, the majority of respondents felt prepared to address "bad news" issues with a patient, 20 and we showed that the participants had retained the key concepts, both immediately following the workshop and in the longer term. 21 In fact, the skill-level at the 6th month point showed a better performance.…”
Section: Discussionmentioning
confidence: 95%
“…Communicating with patients effectively about difficult subjects is important to maintain an effective and productive physician-patient relationship. Significant work has been done to help improve communication about other difficult topics like end-of-life care [ 12 - 14 ]. There are proposed frameworks [ 15 ] on how to communicate effectively about priority setting decisions and further work in this area is warranted.…”
Section: Discussionmentioning
confidence: 99%